Numerical Analysis of Internal Flow Embedded in a Cutting Tool - S. A., Che Ghani; W. S., Wan Harun; M. F. F., Ab Rashid; Rasidi, Ibrahim (2015)
Embedding of internal microchannel into a standard cutting tool alters the thermal and mechanical behaviours of the tool in a machining process which consequently improves the machining performance in terms of wear mechanisms of the tool and surface roughness of the finished product. Obviously conditions of the fluid such as type, temperature, viscosities and speed need to be modelled accurately to determine their effects on the microfluidics performance although the development of ideal mathematical equations to precisely pose a machining process is almost impossible due to the geometrical, physical, thermal and chemical complexities of the process. This work aims at computational fluid dynamics modelling of the internal flow inside the microchannel of 0.8 m diameter to quantify the flow regimes along the cooling manifold for improving the performance of a cutting tool. Two procedures have been performed in this work, namely (1) the determination of flow regimes in the internal microchannel and (2) the mapping of the flow speed topography of the cooling fluid. The fluid in this analysis is assumed to be Newtonian incompressible fluid since it will not change phase while exchanging the heat. The results show that the Reynolds Number in the microchannel manifold are distributed in the range of 528 and 6604 which the numbers higher than 2320 are considered turbulent flow. On the other hand, the empirical correlations show that with the inlet flow rate of 0.3 l/min, the fluid speed at the microchannel part that is closest to heated region can reach up to 7.706 m/min. The outcomes of this work determine the pump capacity of the system and the values obtained from the numerical analysis can be used in the thermodynamics analysis of the cooling performance of the microchannel in removing the heat generated during machining.